The Echo of Die Blechtrommel in Europe Studies on the Reception of Günter Grass's The Tin Drum - Joosten, Jos; Parry, Christoph (Radboud Studies in Humanities, 2016)
The Echo of Die Blechtrommel in Europe presents an overview of the critical reception of Günter Grass's classic novel throughout Europe since its publication in 1959. Readership: The book aims at a relatively broad readership with interest in contemporary European literature and international cultural relations, as well as more specialised readers from (comparative) literary studies interested in Günter Grass, literary institutions and the literary field, reviewing and reception.